Dystrobrevin is required postsynaptically for homeostatic potentiation at the Drosophila NMJ - Salinee Jantrapirom (2019)
© 2019 Elsevier B.V. Evolutionarily conserved homeostatic systems have been shown to modulate synaptic efficiency at the neuromuscular junctions of organisms. While advances have been made in identifying molecules that function presynaptically during homeostasis, limited information is currently available on how postsynaptic alterations affect presynaptic function. We previously identified a role for postsynaptic Dystrophin in the maintenance of evoked neurotransmitter release. We herein demonstrated that Dystrobrevin, a member of the Dystrophin Glycoprotein Complex, was delocalized from the postsynaptic region in the absence of Dystrophin. A newly-generated Dystrobrevin mutant showed elevated evoked neurotransmitter release, increased bouton numbers, and a readily releasable pool of synaptic vesicles without changes in the function or numbers of postsynaptic glutamate receptors. In addition, we provide evidence to show that the highly conserved Cdc42 Rho GTPase plays a key role in the postsynaptic Dystrophin/Dystrobrevin pathway for synaptic homeostasis. The present results give novel insights into the synaptic deficits underlying Duchenne Muscular Dystrophy affected by a dysfunctional Dystrophin Glycoprotein complex.